Recent advancements of nanomaterials as coatings and biocides for the inhibition of sulfate reducing bacteria induced corrosion. (September 2019) - Rasheed, P Abdul; Jabbar, Khadeeja A; Mackey, Hamish R; Mahmoud, Khaled A
Abstract : The control of microbiologically influenced corrosion (MIC) is of great significance in many industrial applications. Attention has been devoted to emerging nanomaterials as 'green' biocides for their remarkable antimicrobial function and relatively low environmental risk. Understanding the antimicrobial inhibition mechanisms is the key to increase the efficiency of nanoparticles and enhance the feasibility of their application against various MIC microorganisms under different environmental conditions. This study gives an overview of the recent advancements of different nanomaterials and nanocomposites used as biocides for the inhibition of MIC. The potential and associated challenges in developing NPs as effective biocides are highlighted.